Dementia with Lewy bodies: Characteristics of the prodromal stage in a nationwide longitudinal cohort: Neuropsychiatry and behavioral neurology: DLB and FTD — clinical manifestations. (7th December 2020) - Blanc, Frédéric; Bouteloup, Vincent; Paquet, Claire; Chupin, Marie; Pasquier, Florence; Gabelle, Audrey; Ceccaldi, Mathieu; Sousa, Paulo Loureiro; Salmon, Pierre Krolak; David, Renaud; Fischer, Clara; Dartigues, Jean‐François; et al.
Abstract: Background: Little is known about the prodromal phase of Dementia with Lewy bodies (DLB). In a large prospective cohort of patients attending memory clinics presenting either subjective cognitive impairment (SCI) and mild neurocognitive impairment (MCI) patients, we undertook an ancillary study aiming at detecting early DLB in a longitudinal framework. Method: We conducted a french nationwide prospective cohort of patients with cognitive complaints and a minimum follow‐up of 4 years. Participants in the Memento cohort study were recruited for either isolated subjective cognitive impairment (SCI) or mild neurocognitive impairment (MCI). Among them, patients from 12 memory resource and research centers, representing eight hundred ninety‐two patients were included in the Lewy sub‐study. Probable Pro‐DLB diagnosis was done using a two‐criteria cut‐off score among the four core clinical features of Dementia with Lewy bodies. This Pro‐DLB group was compared to two other groups: one without any core symptoms (NS group), and the one with one core symptom (1S group). A comprehensive cognitive battery, brain 3D volumetric MRI, CSF, FDG PET and amyloid PET were done. Result: The pro‐DLB group comprised 148 patients (16.6%). Compared to the other two groups, the neuropsychological profile of the pro‐DLB group showed, regarding cognition, more multidomain (59.8%) MCI with slower processing speed, semantic and neurovisual impairment, and regarding behavior, a higher proportion of patients with depression, anxiety, and apathy. Pro‐DLB patients also presented more autonomic symptoms, including lower libido, constipation, rhinorrhea, sicca syndrome, and photophobia. The Pro‐DLB group had isolated lower P‐Tau and no difference in terms of amyloid PET and FDG PET. Brain MRI analysis showed widening of sulci including fronto‐insular, occipital and olfactory sulci (FDR corrected). Evolution to dementia was not different between the three groups after 4 years of follow‐up. Conclusion: Patients with pro‐DLB represented 16.6% of SCI and MCI patients, a finding consistent with the proportion observed at the stage of dementia. In addition to the core symptoms, pro‐DLB patients presented cognitive, behavioral and autonomic symptoms. Biomarkers confirmed the non‐Alzheimer profile. The occipital, fronto‐insular, and olfactory bulb involvement on brain MRI was consistent with the symptoms and known neuropathology.